The Ant Genus Temnothorax Mayr, 1861 (Formicidae: Myrmicinae) in Thailand, with a Description of a New Species - Phosrithong, Netnapa; Ignatius, Kaewpawika Jitthamma; Samung, Yudthana (Tropical Natural History, 2025)
Temnothorax Mayr, 1861, a large ant genus with 502 valid species, 33 valid subspecies, and one valid fossil species (inclu-ding the new species), is predominantly found in temperate regions of the Old and New Worlds. The genus is represented in Thailand by two named species: Temnothorax barrettoi Hamer & Guénard, 2023, and T. sirindhornae Phosrithong, Ignatius & Samung, sp. nov. Herein, Temnothorax sirindhornae sp. nov. is described based on worker and dealate queen castes from the highlands of western Thailand, and T. barrettoi is newly recorded from the country’s lowlands. Notably, both species nest in dead twigs on trees.